Legitimacy, rule of law and violent conflicts in Africa - Alemika, Etannibi (2016)
The aim of this paper is two-fold. First, the paper analyses how citizens in fifteen African countries perceive key elements of governance, including the extent of legitimacy of constitutional, juridical, economic and political systems in Africa as well as perceptions of rule of law and violent conflicts in each of the fifteen countries. Second, the paper investigates the level and source of trust in government institutions. The analysis is based on the round 2 version of the Afrobarometer survey and employs descriptive analysis, factor analysis, scale item reliability analysis as well as OLS multiple regression analysis. Key findings show that the majority of respondents prefer a mixed economy, democratic governance, support the national constitutions and accept that courts and police should enforce the law in the respective countries. Violent conflicts are perceived to be caused by a multitude of factors (not just ethnic and religious factors), but are not acceptable to the respondents as a means of achieving political objectives. Generally, findings show that trust in public institutions is low and that political trust is primarily influenced by how government performs in the arenas of socio-economic management and civil rights protection. Perceptions of corruption among elected and public officials are high. The paper concludes by highlighting that democratic transition in Africa has progressed, but still faces many dangers. The major threats to democratisation are the social, economic and political crises in Africa which have been worsened by IMF/World Bank Structural Adjustment Programmes